Implementasi Layanan Pendidikan Inklusif Untuk Anak Berkebutuhan ADHD di PAUD Terpadu Fly Free - Nita Laelatul Rohmah; Siti Adawiah; Santi Widayanti (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
This study discusses the implementation of inclusive education services for children with special needs ADHD (Attention Deficiency Hyperactivity Disorder) at the Fly Free Integrated PAUD. This research is a qualitative research using a case study approach. Data collection techniques using the results of observation, interviews and documentation. While data analysis uses the Mills and Hubberman analysis model which includes data reduction, data presentation and verification. The benefit of this research is to find out how inclusive education services are in the Fly Free Integrated PAUD. ADHD (Attention Deficit Hyperactivity Disorder) is a group of children with special needs who experience or find difficulties in brain development, hyperactive movement, impulses and difficulty concentrating. There are several things that are needed by children with special needs ADHD (Attention Deficit Hyperactivity Disorder), one of which is school education that implements inclusive education.